Pragnienie i zamiar: przyczynek do dystynkcji pojęć - Seel, Gerhard (ETHICS IN PROGRESS, 2014)
To answer the title question there has been initially introduced the elements of the Aristotle theory in order to confront it with the concepts of the linguistic paradigm philosophers. Finally, the author proposes a very own solution to this dilemma. Accordingly to the methodology of the linguistic paradigm, the paper brings about an analyse of the linguistic expressions to investigate whether they provide a sufficient premise to distinguish between desires and intentions. The author asks several questions which help him describe desires, and them confront achieved characteristics with the essential features of intentions. In conclusion, the paper put forward the case of the explanation of actions according to both desires and intentions